Pharmacokinetics and Pharmacodynamics of Zofenopril in Healthy Volunteers - Marzo, Antonio; Bo, Lorenzo Dal; Mazzucchellia, Paolo; Montia, Nunzia Ceppi; Tettamantia, Rosella Aleotti; Crivellia, Fabrizio; Uhr, Mario Richard; Ismaili, Shevquet; Giusti, Andrea (Arzneimittelforschung, 1999)
This study was carried out to investigate the pharmacokinetics of zofenopril (CAS 81938-43-4) and zofenoprilat, the behaviour of the angiotensin converting enzyme (ACE) (pharmacodynamics) following the administration of zofenopril calcium at the single oral dose of 60 mg in eighteen healthy volunteers.This open label, one-way study was carried out in a single centre on 18 healthy volunteers. The volunteers received an oral single 60 mg dose of zofenopril calcium following an overnight fast. The tablet was swallowed with 250 ml of water. Fasting continued for additional 4 h after dosing and no other liquid intake was allowed from 1 h before to 2 h after administration. Plasma concentrations of zofenopril and its active metabolite zofenoprilat as well as serum ACE activity were measured before drug intake (baseline) and on timed samples over a 36 h period after dosing by LC-MS-MS, a highly sensitive, validated method for active moiety concentrations.Peak plasma concentration was reached on average at 1.19 h with zofenopril and at 1.36 h with zofenoprilat. Concentrations then decreased reaching values under or close to the limit of quantitation (1 ng · ml-1 for zofenopril, 2 ng · ml−1 for zofenoprilat) from 8 to 16 h after dosing. Complete inhibition of ACE was seen at the first blood sampling time (1 h) and lasted on average up to 9.44 h. ACE activity then slowly reactivated, but enzyme inhibition continued and was estimated to be 74% and 56% at 24 and 36 h following drug administration, respectively.From these data a complete or almost complete enzyme inhibition is expected with zofenopril given in repeated dose regimen.
Keywords: Angiotensin converting enzyme inhibitor; CAS 81938-43-4; Zofenopril; pharmacodynamics, pharmacokinetics, plasma concentrations; Zofenoprilat